1991
DOI: 10.1021/ja00009a041
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and photochemical behavior of intramolecular styrene-amine exciplexes

Abstract: The photophysical and photochemical behavior of a series of secondary and tertiary w-(@tyryl)aminoalkanes with one to five methylenes separating the styryl and amino groups has been investigated and compared to the intermolecular reactions of 1 -phenylpropene with secondary and tertiary amines. The tertiary styrylamines form fluorescent intramolecular exciplexes, but fail to undergo intramolecular addition reactions. Both the rate constant for exciplex formation and the stability of the exciplex are dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…On the one hand, some amines could take in reaction in photoinitiated radical systems. [43,44] On the other hand, the tertiary amine moieties of the PDPA block creates alkaline environment, which led the thiol groups to produce thiolate anions. The formation of thiolates prevented thiol groups to be translated into thiyl radials.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, some amines could take in reaction in photoinitiated radical systems. [43,44] On the other hand, the tertiary amine moieties of the PDPA block creates alkaline environment, which led the thiol groups to produce thiolate anions. The formation of thiolates prevented thiol groups to be translated into thiyl radials.…”
Section: Resultsmentioning
confidence: 99%
“…Such scaffold is found in many drugs like unarizine (calcium antagonist) and naine (antifungal). It must be noted that other strategies for the synthesis of allylamines were previously reported in the literature, such as the preparation from alcohols and amines through alkoxyphosphonium salts, 46 the reduction of secondary amides followed by N-methylation 47 or the reduction of propargylamines. 48 Nevertheless, the cited methods require hazardous and expensive reactants, harsh experimental conditions (temperature and pressure) and do not guarantee stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the crude reaction mixture revealed that yield was diminished by the formation of an a-amino adduct 3 (see SI, Table S1 for details), likely promoted by electrostatic interaction between the radical cation of DIPEA and the radical anion of the olefin 1. 18 Consequently, formic acid was added to the reaction mixture, to convert DIPEA into its formate salt and thus prevent formation of aamino radicals. 19 Pleasingly, addition of a slight excess of formic acid relative to DIPEA improved the yield to 82%, with no traces of the a-amino adducts detected in the 1 H NMR spectrum of the crude reaction mixture (Table 1, entry 6).…”
Section: Resultsmentioning
confidence: 99%